2017
DOI: 10.1063/1.4995220
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium-doped MoS2 films

Abstract: Tailoring the electrical properties of transition metal dichalcogenides by doping is one of the biggest challenges for the application of 2D materials in future electronic devices. Here, we report on a straightforward approach to the n-type doping of molybdenum disulfide (MoS2) films with rhenium (Re). High-Resolution Scanning Transmission Electron Microscopy and Energy-Dispersive X-ray spectroscopy are used to identify Re in interstitial and lattice sites of the MoS2 structure. Hall-effect measurements confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 35 publications
4
38
1
Order By: Relevance
“…No Raman changes were observed, and in particular no sign of ReS2 formation. TEM showed Re in Mo sites, and a small increase in the in-plane lattice spacing, while scanning tunneling microscopy (STM) suggested Mo substitution within grains and intercalation at grain boundaries [177]. Another STM study also showed Mo substitution by Re [178].…”
Section: Structure Of Doped Mos2mentioning
confidence: 98%
“…No Raman changes were observed, and in particular no sign of ReS2 formation. TEM showed Re in Mo sites, and a small increase in the in-plane lattice spacing, while scanning tunneling microscopy (STM) suggested Mo substitution within grains and intercalation at grain boundaries [177]. Another STM study also showed Mo substitution by Re [178].…”
Section: Structure Of Doped Mos2mentioning
confidence: 98%
“…Hallam et al also demonstrated the scalable synthesis of Re-doped MoS 2 films with electron concentrations in the range of 5 × 10 17 to 9 × 10 17 cm −3 as determined via Hall effect measurements and supported by DFT calculations. In their approach, the authors used "thermally-assisted conversion" (TAC), similar to the method used by Lasker et al to synthesize Nb-doped p-type MoS 2 films [405], to convert interleaved Mo-Re films into Re-doped MoS 2 via high-temperature sulfurization [411]. However, the electron mobility of their Re-doped MoS 2 films was low, ranging between 0.1 to 0.7 cm 2 /V-s, implying the presence of various carrier scattering sources (including scattering from the incorporated Re dopant atoms).…”
Section: Electron Doping By Cation Substitutionmentioning
confidence: 99%
“… 27 , 36 In most cases, substitutionally doped MoS 2 is synthesized by high-temperature sulfurization (900 °C is not uncommon) of an alloy or a nanolaminate of metallic Mo and the pure dopant. 37 Substitutional doping of TMDs with, for example, Nb, 27 Er, 38 C, 28 Ti, 39 Zn, 15 and Cl, 36 has already been reported using this strategy, resulting in mainly n -type doping, in a few instances,in p -type doping, and inmost cases this approach exhibited limited control over the dopant level.…”
Section: Introductionmentioning
confidence: 99%